Correction (Journal of Maps)
Article title: Mining Tailings Dumps and Socio-territorial Inequalities in Chile: An exploratory studyAuthors: Iván Ojeda-Pereira, Hernan Pezoa-Quevedo, and Fernando Campos-MedinaJournal: Journal of MapsDOI: https://doi.org/10.1080/17445647.2023.2217514 An appendix containing low resolution versions of the supplementary maps has been added.